A positive electrode material and preparation method thereof, a positive electrode sheet and an O3-type layered sodium ion battery

By doping metal elements with f-electron orbitals in the positive electrode material of O3-type layered sodium ion battery, such as Pr, Nd, Sm, etc., and entangling their electron orbitals with the d-electron orbitals of Ni, Fe and Mn elements, the irreversible phase change, dynamics problems and air sensitivity of the positive electrode material are solved, and the electrochemical performance of the battery is significantly improved.

CN115207339BActive Publication Date: 2025-04-29JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211022666.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-04-29
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

The positive electrode material of O3 layered sodium ion battery has complex irreversible phase change and slow kinetic problems, resulting in rapid capacity drop and poor rate performance. It is also sensitive to air and easily damaged structure.

Method used

NaM1-x-y-zNixFeyMnzO2 is used as the cathode material, where M includes a first metal element with an f-electron orbital, such as Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm and Yb. By doping these elements, entangle their electron orbitals with the d-electron orbitals of Ni, Fe and Mn elements, improve the structure and air stability of the material, and increase the ion diffusion channel of sodium ions.

Benefits of technology

The electrochemical performance of the cathode material is significantly improved, including structural stability, rate performance and energy density, reducing capacity reduction and sensitivity to air, and improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115207339B_ABST
    Figure CN115207339B_ABST
Patent Text Reader

Abstract

The present invention discloses a cathode material, a preparation method thereof, a cathode electrode sheet, and an O3-type layered sodium-ion battery, relating to the technical field of batteries; the chemical formula of the cathode material is NaM 1‑x‑y‑ z Ni x Fe y Mn z O2; M includes a first metal element having an f electron orbital. The Ni, Fe, and Mn elements in the cathode material are all elements containing d electron orbitals. Through the doping of the M element, on the one hand, the f electron orbital can be entangled with the d electron orbital, and the performance of the cathode material can be improved synergistically to enhance the structural and air stability of the material; on the other hand, it can also facilitate the interaction of various elements in the material, enabling ions to move away from their original positions to generate vacancies, increasing the ionic diffusion channels of sodium ions, and improving the rate performance of the material. In addition, it can also stimulate the redox reaction of oxygen atoms in anions during charge and discharge, improving the energy density and power density of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and an O3 type layered sodium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in the field of energy equipment. However, the existing lithium element on the earth is very limited, which has caused widespread doubts about whether lithium resources can meet future demand. One way to solve this problem is to develop energy storage devices based on other carriers. Sodium-ion batteries are expected to meet future energy storage needs due to the advantages of abundant sodium resources and low cost, as well as physical and chemical properties similar to lithium-ion batteries. However, since the relative molecular mass of sodium is higher than that of lithium, and the radius of sodium ions is also larger than that of lithium ions, the energy density of sodium-ion batteries will be lower than that of lithium-ion batteries, which greatly hinders the commercial development of sodium-ion batteries. Therefore, the development of high-performance electrode materials is the first problem that needs to be solved for sodium-ion batteries to move towards application.

[0003] Among various cathode materials for sodium-ion batteries, O3-NaNi 0.5 Mn 0.5 O2 has attracted extensive attention due to its advantages of providing sufficient sodium in full batteries, high electrochemical activity, high theoretical specific capacity and easy synthesis. However, it has complex irreversible phase transitions and slow kinetics, which lead to rapid capacity decline and poor rate performance. In addition, the limitations of O3-NaNi 0.5 Mn 0.5 Another major problem in the application of O2 is that it is particularly sensitive to air. When exposed to air, its structure will be destroyed and its electrochemical performance will deteriorate.

[0004] To this end, the existing technology usually uses doping with heterogeneous elements to improve the above problems. Wang et al. prepared Al-doped NaAl by sol-gel method. 0.2 Ni 0.49 Mn 0.49 O2 material. At a current density of 240 mA g -1 The capacity retention rate of the 2 mol% Al-doped material after 200 cycles is 63.2%, which is higher than that of NaNi 0.5 Mn 0.5 O2 is 21.4% higher. Although this method has improved the material performance, it is still far from practical application. Komaba et al. 0.5 Mn 0.5 Fe is introduced into O2 material 3+ , thus obtaining NaNi 0.4 Mn 0.4 Fe 0.2O2 undergoes a more reversible phase change in the high voltage region. Its capacity is 125mAh-1 in the voltage range of 2-3.8V, and its first-week capacity is 185mAhg-1 in the voltage range of 2.2-4.5V. Although the trend of phase transition is suppressed, it is still difficult to overcome the disadvantage that the material is sensitive to air and water, resulting in failure of the material structure.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a positive electrode material with excellent and stable electrochemical performance and a preparation method thereof and a positive electrode sheet, which can effectively improve the electrochemical performance of an O3 type layered sodium ion battery.

[0007] Another object of the present invention is to provide an O3 type layered sodium ion battery, which comprises the above-mentioned positive electrode material. Therefore, it also has the advantage of higher electrochemical performance.

[0008] The embodiment of the present invention is achieved as follows:

[0009] In a first aspect, the present invention provides a positive electrode material for an O3-type layered sodium ion battery, wherein the chemical formula of the positive electrode material is NaM 1-x-y-z Ni x Fe y Mn z O2, x, y and z are all positive numbers less than 1;

[0010] Wherein, M includes a first metal element, and the first metal element has an f electron orbital.

[0011] In an alternative embodiment, the first metal element includes at least one of Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm and Yb.

[0012] In an alternative embodiment, the first metal element further has a d electron orbital.

[0013] In an alternative embodiment, the first metal element includes at least one of Ce, Gd and Lu; x=0.01 or 0.1.

[0014] In an optional embodiment, M further includes a second metal element, and the second metal element has a d electron orbital.

[0015] In an alternative embodiment, the second metal element includes at least one of Ti, Cr, Mn, Zn, Ag and Mo.

[0016] In an optional embodiment, 01≤x≤1, 0.01≤y≤1, 0.01≤z≤1.

[0017] In a second aspect, the present invention provides a method for preparing a positive electrode material according to any one of the aforementioned embodiments, comprising:

[0018] The positive electrode precursor salt, sodium salt and M metal salt are uniformly mixed in proportion to form a mixture, and solid-phase sintering is performed to obtain a positive electrode material.

[0019] In a third aspect, the present invention provides a positive electrode plate, comprising the positive electrode material of any one of the aforementioned embodiments; or, comprising the positive electrode material prepared by the preparation method of the positive electrode material of the aforementioned embodiments.

[0020] In a fourth aspect, the present invention provides an O3-type layered sodium ion battery, comprising the positive electrode sheet of the aforementioned embodiment.

[0021] The embodiments of the present invention have at least the following advantages or beneficial effects:

[0022] The embodiment of the present invention provides a positive electrode material and a preparation method thereof, wherein the positive electrode material is used for an O3 type layered sodium ion battery, and the chemical formula of the positive electrode material is NaM 1-x-y-z Ni x Fe y Mn z O2, x, y and z are all positive numbers less than 1; wherein M includes a first metal element, and the first metal element has an f electron orbital. Ni, Fe and Mn elements in the positive electrode material are all elements containing d electron orbitals. Therefore, through the doping of M element, on the one hand, the f electron orbitals in M ​​element can be entangled with the d electron orbitals in Ni, Fe and Mn elements and synergistically improve the performance of the positive electrode material to improve the structure and air stability of the material; on the other hand, it can also facilitate the interaction between the elements in the material so that the ions can move away from their original positions to generate vacancies. The generation of vacancies can increase the ion diffusion channel of sodium ions to improve the rate performance of the material and ensure the electrochemical performance of the battery. In addition, it can also stimulate the redox reaction of oxygen atoms in anions during the charge and discharge process of the material, effectively improving the energy density and power density of the material.

[0023] The embodiments of the present invention also provide a positive electrode sheet and an O3-type layered sodium ion battery, which include the above-mentioned positive electrode material. Therefore, they also have the advantage of higher electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 The crystal structure diagram of Na2MnO4 provided by the present invention;

[0026] Figure 2 The NaNi provided by the present invention 0.5 Mn 0.5 The crystal structure of O2;

[0027] Figure 3 A scanning electron microscope image of the positive electrode material provided in Example 1 of the present invention;

[0028] Figure 4 This is the first cycle charge and discharge characteristic curve of the battery provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0030] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0031] Based on the limited effect of improving the electrochemical performance of sodium ion batteries by doping elements in the prior art, the embodiments of the present invention provide a positive electrode material with excellent and stable electrochemical performance, a preparation method thereof, and a positive electrode sheet, which can effectively improve the electrochemical performance of O3-type layered sodium ion batteries.

[0032] In the embodiment of the present invention, the positive electrode material provided is used for O3 type layered sodium ion battery, and of course, it can also be used for other batteries if conditions permit. At the same time, the chemical formula of the positive electrode material is NaM 1-x-y-z Ni x Fe y Mn z O2, x, y and z are all positive numbers less than 1; wherein M includes a first metal element, and the first metal element has an f electron orbital.

[0033] In the above positive electrode materials, the Ni, Fe and Mn elements in the materials are all elements containing d electron orbitals. Therefore, through the doping of the M element, on the one hand, the f electron orbitals in the M element can be entangled with the d electron orbitals in the Ni, Fe and Mn elements and synergistically improve the performance of the positive electrode material to improve the structure and air stability of the material; on the other hand, it can also facilitate the interaction between the elements in the material so that the ions can move away from their original positions to generate vacancies. The generation of vacancies can increase the ion diffusion channel of sodium ions to improve the rate performance of the material and ensure the electrochemical performance of the battery. In addition, it can also stimulate the redox reaction of oxygen atoms in the anions of the material during the charge and discharge process, effectively improving the energy density and power density of the material.

[0034] It should be noted that, in this embodiment, 01≤x≤1, 0.01≤y≤1, 0.01≤z≤1; preferably, 0.2≤x≤0.4, 0.2≤y≤0.4, 0.2≤z≤0.4. By controlling the proportion of each element, the entanglement interaction effect of the d electron orbital and the f electron orbital can be maximized to fully ensure the electrochemical performance of the battery.

[0035] It should also be noted that the first metal element containing f electron orbitals can be selected from at least one of Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm and Yb. Such first metal elements only contain f electron orbitals and do not have d electron orbitals, and can be entangled with the d electron orbitals in Ni, Fe and Mn elements to improve the stability of the material and the electrochemical properties of the material, thereby fully improving the electrochemical properties of the battery.

[0036] Exemplarily, in an embodiment of the present invention, the first metal element can be specifically selected as Yb or Tb. Yb or Tb elements are rare metal elements, and have f electron orbits that can be entangled with d electron orbits, and can fully improve the electrochemical properties and stability of the material through the entanglement of electron orbits. At the same time, when the first metal element is specifically selected as Yb, x can be selected as 0.2 or 0.5; when the first metal element is selected as Tb, x can be selected as 0.2. While selecting a specific metal element, the ratio of each element is controlled so that the entanglement of the electron orbit can make the components of the positive electrode material cooperate with each other to produce vacancies, so as to increase the ion diffusion channel of sodium ions, thereby fully improving the rate performance of the material and improving the electrochemical performance of the battery.

[0037] Of course, in this embodiment, the first metal element may also have a d electron orbital, and by reintroducing the d electron orbital, the d electron orbital can be supplemented so that the d electron orbital can be fully entangled with the f electron orbital and fully interact with each other to effectively improve the electrochemical performance and stability of the material. Exemplarily, when the first metal element includes both a d electron orbital and an f electron orbital, the first metal element includes at least one of Ce, Gd and Lu, and x = 0.01 or 0.1. While selecting a specific metal element, the ratio of each element is controlled so that the entanglement of the electron orbital can not only improve the stability of the material, but also make the components of the positive electrode material cooperate with each other to generate vacancies to increase the ion diffusion channel of the sodium ion, thereby fully improving the rate performance of the material and improving the electrochemical performance of the battery.

[0038] As an optional scheme, in an embodiment of the present invention, M also includes a second metal element, and the second metal element has a d electron orbital. The addition of the second metal element can further supplement the d electron orbital to better cooperate with the f electron orbital to improve the electrochemical performance and stability of the material. Exemplarily, the second metal element includes at least one of Ti, Cr, Mn, Zn, Ag and Mo. The difference between the second metal element and the first metal element is that the first metal element must have an f electron orbital, preferably also a d electron orbital, while the second metal element only has a d electron orbital, which is used to supplement or adapt the first metal element to fully ensure the electrochemical performance of the battery.

[0039] An embodiment of the present invention further provides a method for preparing the above-mentioned positive electrode material, which comprises uniformly mixing a positive electrode precursor salt, a sodium salt, and an M metal salt in proportion to form a mixture, and solid-phase sintering to obtain the positive electrode material.

[0040] In detail, the positive electrode precursor salt includes nickel salt, manganese salt and iron salt. For example, the corresponding material can be selected from nickel oxide, nickel iron oxide, nickel iron manganese oxide, manganese oxide, iron oxide, manganese iron oxide, nickel manganese oxide, nickel hydroxide, iron hydroxide, manganese hydroxide, nickel iron hydroxide, nickel iron manganese hydroxide, and nickel manganese hydroxide. Sodium salt can be selected as sodium carbonate, sodium hydroxide, sodium oxide, sodium peroxide, sodium phosphate, sodium sulfate, sodium dihydrogen phosphate, sodium dihydrogen sulfate, sodium phenol, etc. M metal salt can be selected according to the corresponding metal salt containing f electron orbit and d electron orbit, for example, it can be selected from cerium oxide, titanium oxide, samarium oxide, lutetium oxide, dysprosium oxide, molybdenum oxide and other materials.

[0041] It should be noted that Figure 1 The crystal structure diagram of Na2MnO4 provided by the present invention; Figure 2 The NaNi provided by the present invention 0.5 Mn 0.5The raw materials in this embodiment can be mixed by direct contact and then low-temperature sol-gel mixing, or by high-energy ball milling. The mixed mixture needs to be exposed to an oxidizing gas (the oxidizing gas can be oxygen or compressed air) or air, and then the mixture is solid-state sintered at a heating temperature of 625°C to 1210°C; the holding time is 0.5-20h. In addition, during the solid-phase sintering process, the material is based on Figure 1 The crystal structure of Na2MnO4 shown in Figure 1 evolves into Figure 2 The NaNi 0.5 Mn 0.5 The crystal structure of O2, thus obtaining the material NaM 1-x-y- z Ni x Fe y Mn z O2.

[0042] For example, the positive electrode material can be selected from sodium carbonate, nickel iron manganese hydroxide and terbium oxide mixed in a molar ratio of a:b:c. Among them, c is in the range of 0.01 to 1, preferably 0.25 or 0.0375, a is in the range of 0.55 or 0.525, and b is approximately 1. By configuring the molar ratio in this way, it can be ensured that the raw materials are fully contacted to ensure the preparation efficiency and quality of the material.

[0043] It should be noted that the molecular formula of the positive electrode material in the embodiments of the present invention is detected by ICP. The full name of ICP-AES is Inductively Coupled Plasma-Atomic Emission Spectrometry, also known as Inductively Coupled Plasma-OES, which will not be described in detail in the embodiments of the present invention.

[0044] An embodiment of the present invention further provides a positive electrode plate, which is prepared by the above-mentioned positive electrode material. Among them, the positive electrode plate may include a current collector and a positive electrode active material layer arranged on at least one side of the current collector. The positive electrode active material layer is obtained by coating the positive electrode slurry on the current collector, drying it and cold pressing it. The positive electrode slurry includes a positive electrode material, a conductive agent, a binder and a solvent. Among them, the current collector can be selected as aluminum foil, the conductive agent and the binder each account for less than or equal to 5%, the conductive agent can be selected as carbon black, carbon nanotubes, graphene, etc., the binder can be selected as polyvinylidene fluoride (PVDF), and the solvent can be selected as N-methylpyrrolidone (NMP).

[0045] Specifically, when preparing the positive electrode sheet, the prepared raw materials can be weighed first, and the positive electrode material: conductive carbon: PVDF are mixed in a mass ratio of 90:5:5, and then dissolved in a certain amount of NMP. After stirring evenly, it is coated on the current collector, and then dried and cut into pieces to obtain the positive electrode sheet.

[0046] Since the positive electrode plate includes the above-mentioned positive electrode material, the positive electrode plate also has the advantage of being able to improve the electrochemical performance of the battery.

[0047] An embodiment of the present invention further provides an O3-type layered sodium-ion battery, comprising the positive electrode sheet of the aforementioned embodiment. Moreover, the O3-type layered sodium-ion battery specifically comprises a housing, a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte. Among them, the positive electrode sheet, the separator and the negative electrode sheet are stacked, and a bare cell is formed by stacking or winding. The bare cell is loaded into the housing and the electrolyte is injected to obtain a battery. Among them, the negative electrode sheet may include a current collector and a negative active material layer, and the current collector may be selected as copper foil. The negative active material layer is obtained by coating the negative active slurry on the current collector, drying and cold pressing. Among them, the negative active slurry includes a negative electrode material, a conductive agent, a binder, a dispersant and a solvent. The amount of conductive agent and binder is less than or equal to 10%, and the negative electrode material can be selected from soft carbon, hard carbon or composite carbon, etc. The conductive agent can be selected from conductive carbon black, conductive graphite, vapor-grown carbon fiber, carbon nanotubes, etc. The binder can be selected from styrene-butadiene rubber, the dispersant can be selected from CMC, and the solvent can be selected from N-methylpyrrolidone (NMP). The electrolyte is obtained by dissolving 1M sodium hexafluorophosphate in a solvent with a volume ratio of EC:PC=1:1.

[0048] Specifically, when preparing the negative electrode sheet, the raw materials to be prepared can be weighed first, and the negative electrode hard carbon material: conductive carbon: CMC / SBR are mixed in a mass ratio of 80:10:10, and then dissolved in a certain amount of NMP. After stirring evenly, the mixture is coated on the current collector, and then dried and cut into pieces to obtain the negative electrode sheet.

[0049] Since the O3 type layered sodium ion battery includes the above-mentioned positive electrode material, the O3 type layered sodium ion battery also has the characteristics of excellent electrochemical performance.

[0050] The preparation process and performance of the battery are described in detail below in conjunction with specific examples and comparative examples:

[0051] Example 1

[0052] This embodiment provides an O3 type layered sodium ion battery, which is prepared by the following method:

[0053] S1: Preparation of positive electrode sheet, step S1 specifically includes:

[0054] S11: Preparation of positive electrode materials;

[0055] Step S11 specifically includes: placing the precursor sodium carbonate, nickel iron manganese hydroxide and terbium oxide in a high-energy ball mill according to a certain stoichiometric amount and placing it on a ball mill. Ball milling is performed at a speed of 3000 rpm for 1.05 hours, and the precursor particles are heated and dried in a vacuum oven to obtain precursor particles. The precursor particles are quickly transferred to a high-temperature solid phase sintering furnace, and compressed air or oxygen is protected in an appropriate proportion in the furnace. The heating rate is 1-10°C / min and heated at 815°C for 9.5 hours to obtain NaTb 0.2 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material. The SEM morphology of the prepared positive electrode material is shown in Figure 3 shown.

[0056] S12: Preparation of pole piece;

[0057] Step S12 specifically includes: mixing the positive electrode material: conductive carbon SP: PVDF in a mass ratio of 90:5:5, then dissolving in a certain amount of NMP, stirring evenly and coating on both sides of the current collector, and drying and cutting to obtain the positive electrode sheet.

[0058] S2: Preparation of negative electrode sheet:

[0059] Step S2 specifically includes mixing the negative electrode hard carbon material: conductive carbon: CMC / SBR in a mass ratio of 80:10:10, then dissolving in a certain amount of NMP, stirring evenly and coating on the current collector, and drying and cutting to obtain the negative electrode sheet.

[0060] S3: After the positive electrode sheet, separator and negative electrode sheet are arranged in sequence and wound to prepare a bare battery cell, the bare battery cell is placed in a shell and then injected with electrolyte; the battery after injection is left to stand, pre-charged, exhaust gas is extracted, sealed, and capacity is divided to prepare an O3-type layered sodium-ion battery. The O3-type layered sodium-ion battery is a button battery, and the weight of the positive electrode sheet of a single battery is approximately 1mg to 1.5mg.

[0061] Example 2

[0062] Example 2 provides an O3-type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0063] Step S11 specifically includes: contacting sodium carbonate, terbium oxide, nickel nitrate, ferrous oxalate and manganese oxide to form a mixed powder; placing the mixed powder in a ball mill, and using an ethanol organic solvent to ball mill and stir for 2.5 hours at a speed of 1400 rpm to prepare a precursor material and vacuum drying; quickly transferring to a high-temperature solid phase sintering furnace, while protecting with compressed air or oxygen in the furnace; after protecting and heating at 925°C for 12.5 hours, removing the material and adding terbium oxide, continuing ball milling for 0.5 hours, transferring to a furnace for secondary sintering at a temperature of about 885°C, and keeping warm for 10 hours to obtain NaTb 0.2 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material.

[0064] Example 3

[0065] Example 3 provides an O3 type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0066] Step S11 specifically includes: placing sodium carbonate, nickel iron manganese hydroxide and samarium oxide in a high-energy ball mill according to a certain stoichiometric amount and placing it on a ball mill; ball milling at a speed of 3000 rpm for 1.05 hours, heating in a vacuum oven and drying to prepare a precursor; rapidly transferring to a high-temperature solid phase sintering furnace, while protecting the furnace with compressed air or oxygen in an appropriate proportion, heating at a rate of 1-10°C / min at 815°C for 9.5 hours to obtain NaSm 0.2 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material.

[0067] Example 4

[0068] Example 4 provides an O3 type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0069] Step S11 specifically includes: placing sodium carbonate, nickel iron manganese hydroxide, samarium oxide and cerium oxide in a high-energy ball mill according to a certain stoichiometric amount and placing it on a ball mill; ball milling at a speed of 3000 rpm for 2 hours, heating in a vacuum oven and drying to prepare a precursor; rapidly transferring to a high-temperature solid phase sintering furnace, while protecting the furnace with compressed air or oxygen in an appropriate proportion, heating at a rate of 1-10°C / min at 820°C for 10 hours to obtain NaCe 0.1 Sm 0.1 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material.

[0070] Example 5

[0071] Example 5 provides an O3-type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0072] Step S11 specifically includes: placing sodium carbonate, nickel iron manganese hydroxide, ytterbium oxide and cerium oxide in a high-energy ball mill according to a certain stoichiometric amount and placing it on a ball mill; ball milling at a speed of 3000 rpm for 2.1 hours, heating in a vacuum oven and drying to prepare a precursor; rapidly transferring to a high-temperature solid phase sintering furnace, while protecting the furnace with compressed air or oxygen in an appropriate proportion, heating at a rate of 1-10°C / min at 830°C for 9 hours to obtain NaCe 0.1 Yb 0.1 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material.

[0073] Example 6

[0074] Example 6 provides an O3-type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0075] Step S11 specifically includes: placing sodium carbonate, nickel iron manganese hydroxide, molybdenum oxide and samarium oxide in a high-energy ball mill according to a certain chemical amount and placing it on a ball mill; ball milling at a speed of 3000 rpm for 1.9 hours, heating in a vacuum oven and drying to prepare a precursor; rapidly transferring to a high-temperature solid phase sintering furnace, while protecting the furnace with compressed air or oxygen in an appropriate proportion, heating at a rate of 1-10°C / min at 850°C for 8.5 hours to obtain NaSm 0.1 Mo 0.1 Ni 0.2 Fe 0.3 Mn 0.3 O2 positive electrode material.

[0076] Example 7

[0077] Example 7 provides an O3-type layered sodium ion battery, and its preparation method is different from that of Example 1 in that:

[0078] Step S11: The positive electrode material prepared is NaTb 0.1 Ni 0.1 Fe 0.3 Mn 0.5 O2.

[0079] Example 8

[0080] Example 8 provides an O3-type layered sodium ion battery, and its preparation method is different from that of Example 2 in that:

[0081] Step S11: The positive electrode material prepared is NaTb 0.1 Ni 0.1 Fe 0.3 Mn 0.5 O2.

[0082] Example 9

[0083] Example 9 provides an O3 type layered sodium ion battery, and its preparation method is different from that of Example 2 in that:

[0084] Step S11: The positive electrode material prepared is NaSm 0.2 Ni 0.2 Fe 0.3 Mn 0.3 O2.

[0085] Comparative Example 1

[0086] Comparative Example 1 provides an O3-type layered sodium ion battery, the preparation method of which is different from that of Example 1 in that:

[0087] Step S11: The positive electrode material prepared is NaNi 0.4 Fe 0.3 Mn 0.3 O2.

[0088] Comparative Example 2

[0089] Comparative Example 2 provides an O3-type layered sodium ion battery, the preparation method of which is different from that of Example 2 in that:

[0090] Step S11: The positive electrode material prepared is NaNi 0.4 Fe 0.3 Mn 0.3 O2.

[0091] Experimental Example 1

[0092] The O3-type layered sodium ion battery provided in Examples 1-9 and Comparative Examples 1-2 was subjected to a discharge specific capacity test at a current density of 1C. The test conditions were charge first and then discharge, constant current charging, and the current was the calculated current corresponding to 1C. (For example, the design capacity is 1Ah, the 1C current density is 1mA / g, the current is calculated and input into the system in combination with the cell mass and the positive electrode sheet load, and the voltage range is 2-4V.) The test results are shown in Figures 1, Figure 4 As shown. Among them, Figure 4 This is a result diagram of Example 1. Method 1 in Table 1 refers to the preparation method of Example 1, and Method 2 refers to the preparation method of Example 2.

[0093] Table 1. Discharge specific capacity test results

[0094]

[0095] According to the comparison of Examples 1-9 and Comparative Examples 1-2 in Table 1, and Figure 1 and Figure 2 It can be seen from the data that the embodiments of the present invention can prepare a positive electrode material in the form of a pellet by doping a metal element with an f electron orbital, which can effectively improve the discharge specific capacity of the battery. According to the comparison of the data of Examples 1, 3-6 and Examples 2, 8-9, it can be seen that the preparation method of the positive electrode material provided in Example 1 can better improve the discharge specific capacity of the battery and ensure the electrochemical performance of the battery. The preparation method of the positive electrode material provided in Example 2 can also improve the electrochemical performance of the battery to a certain extent, but the improvement is less than the method used in Example 1. According to the data of Examples 1, 2-6 and Example 7, when 0.2≤x≤0.4, 0.2≤y≤0.4, and 0.2≤z≤0.4 are all controlled within the corresponding range, the discharge specific capacity of the battery can be better improved to ensure the electrochemical performance of the battery.

[0096] Experimental Example 2

[0097] The O3-type layered sodium ion batteries provided in Examples 1-9 and Comparative Examples 1-2 were subjected to coulombic efficiency tests, and the test conditions were charge first and then discharge, constant current charging, and the current was 1C corresponding to the calculated current. (For example, the design capacity is 1Ah, the 1C current density is 1mA / g, the current is calculated and input into the system in combination with the cell mass and the positive electrode load, and the voltage range is 2-4V.), and the test results are shown in Table 2. Method 1 in Table 2 refers to the preparation method of Example 1, and Method 2 refers to the preparation method of Example 2.

[0098] Table 2. Results of the first coulombic efficiency test

[0099]

[0100] According to the data in Table 2, the embodiments of the present invention can prepare a positive electrode material in the form of a pellet by doping a metal element having an f electron orbital, which can effectively improve the first coulombic efficiency of the battery. According to the data comparison between Examples 1, 3-6 and Examples 2, 8-9, it can be seen that the preparation method of the positive electrode material provided in Example 1 can better improve the first coulombic efficiency of the battery and ensure the electrochemical performance of the battery. The preparation method of the positive electrode material provided in Example 2 can also improve the electrochemical performance of the battery to a certain extent, but the improvement is less than the method used in Example 1. According to the data of Examples 1, 2-6 and Example 7, when 0.2≤x≤0.4, 0.2≤y≤0.4, and 0.2≤z≤0.4 are all controlled within the corresponding range, the first coulombic efficiency of the battery can be better improved to ensure the electrochemical performance of the battery.

[0101] Experimental Example 3

[0102] The O3-type layered sodium ion batteries provided in Examples 1-9 and Comparative Examples 1-2 were tested for rate performance at current densities of 0.5 / 2 / 5C, respectively. The test conditions were charge first and then discharge, constant current charging, and the current was 1C corresponding to the calculated current. (For example, the design capacity is 1Ah, the 1C current density is 1mA / g, the current is calculated and input into the system in combination with the cell mass and the positive electrode sheet load, and the voltage range is 2-4V.), and the test results are shown in Table 3. Method 1 in Table 3 refers to the preparation method of Example 1, and Method 2 refers to the preparation method of Example 2.

[0103] Table 3. Rate performance test results

[0104]

[0105] According to the data in Table 3, the embodiments of the present invention can prepare a positive electrode material in the form of a pellet by doping a metal element having an f electron orbital, which can effectively improve the rate performance of the battery. According to the data comparison between Examples 1, 3-6 and Examples 2, 8-9, it can be seen that the method for preparing the positive electrode material provided in Example 1 can better improve the rate performance of the battery and ensure the electrochemical performance of the battery. The method for preparing the positive electrode material provided in Example 2 can also improve the electrochemical performance of the battery to a certain extent, but the improvement is less than the method used in Example 1. According to the data of Examples 1, 2-6 and Example 7, when 0.2≤x≤0.4, 0.2≤y≤0.4, and 0.2≤z≤0.4 are all controlled within the corresponding range, the rate performance of the battery can be better improved and the electrochemical performance of the battery can be ensured.

[0106] Experimental Example 4

[0107] The O3-type layered sodium ion batteries provided in Examples 1-9 and Comparative Examples 1-2 were subjected to air stability tests at current densities of 0.5 / 2 / 5C, respectively. The test conditions were that the comparative capacity was tested after exposure to air for 30 days. The test results are shown in Table 4. In Table 4, Method 1 refers to the preparation method of Example 1, and Method 2 refers to the preparation method of Example 2.

[0108] Table 4. Air stability test results

[0109]

[0110] According to the data in Table 4, the embodiments of the present invention can prepare a positive electrode material in the form of a pellet by doping a metal element with an f electron orbital, which can effectively improve the air stability of the battery. According to the data comparison between Examples 1, 3-6 and Examples 2, 8-9, it can be seen that the preparation method of the positive electrode material provided in Example 1 can better improve the air stability of the battery and ensure the electrochemical performance of the battery. The preparation method of the positive electrode material provided in Example 2 can also improve the air stability of the battery to a certain extent, but the improvement is less than the method used in Example 1. According to the data of Examples 1, 2-6 and Example 7, when 0.2≤x≤0.4, 0.2≤y≤0.4, and 0.2≤z≤0.4 are all controlled within the corresponding range, the air stability of the battery can be better improved and the electrochemical performance of the battery can be ensured.

[0111] According to the data in Tables 1-4 above, the Ni, Fe and Mn elements in the positive electrode materials provided by the embodiments of the present invention are all elements containing d electron orbitals, which are doped with the M element. On the one hand, the f electron orbitals in the M element can be mutually entangled with the d electron orbitals in the Ni, Fe and Mn elements and synergistically improve the performance of the positive electrode material to improve the structure and air stability of the material; on the other hand, it can also facilitate the interaction between the elements in the material so that the ions can move away from their original positions to produce vacancies, and the generation of vacancies can increase the ion diffusion channel of the sodium ions to improve the rate performance of the material and ensure the electrochemical performance of the battery. In addition, the redox reaction of oxygen atoms in the anions of the material during the charge and discharge process can be stimulated, effectively improving the energy density and power density of the material.

[0112] In summary, the embodiments of the present invention provide a positive electrode material with excellent and stable electrochemical performance and a preparation method thereof and a positive electrode sheet, which can effectively improve the electrochemical performance of an O3-type layered sodium ion battery. The embodiments of the present invention also provide an O3-type layered sodium ion battery, which includes the above-mentioned positive electrode material. Therefore, it also has the advantage of high electrochemical performance.

[0113] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode material for an O3 type layered sodium ion battery, characterized in that: The chemical formula of the positive electrode material is NaM 1-x-y-z Ni x Fe y Mn z O2, x, y and z are all positive numbers less than 1, 0.2≤x≤0.4, 0.2≤y≤0.4, 0.2≤z≤0.4; Wherein, M comprises a first metal element, and the first metal element has an f electron orbital; The first metal element includes at least one of Pr, Nd, Sm, Eu, Tb, Dy, Ho, Er, Tm and Yb.

2. The positive electrode material according to claim 1, characterized in that: The first metal element also has a d electron orbital.

3. The positive electrode material according to claim 2, characterized in that: The first metal element includes at least one of Ce, Gd and Lu; x=0.01 or 0.

1.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that: M also includes a second metal element having a d electron orbital.

5. The positive electrode material according to claim 4, characterized in that: The second metal element includes at least one of Ti, Cr, Mn, Zn, Ag, and Mo.

6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: include: The positive electrode precursor salt, the sodium salt and the M metal salt are uniformly mixed in proportion to form a mixture, and solid-phase sintering is performed to obtain the positive electrode material.

7. A positive electrode sheet, characterized in that: The positive electrode material comprises any one of claims 1 to 5; or the positive electrode material prepared by the method for preparing the positive electrode material according to claim 6.

8. An O3 type layered sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 7.

Citation Information

Patent Citations

  • Iron-based layered oxide positive electrode active material and preparation method and application thereof

    CN113716622A